Reticulate Pleistocene evolution of Ethiopian rodent genus along remarkable altitudinal gradient - Bryja, Josef; Kostin, Danila; Meheretu, Yonas; Šumbera, Radim; Bryjová, Anna; Kasso, Mohammed; Mikula, Ondřej; Lavrenchenko, Leonid A (Molecular phylogenetics and evolution, 2018)
The Ethiopian highlands are the most extensive complex of mountainous habitats in Africa. The presence of the Great Rift Valley (GRV) and the striking elevational ecological gradients inhabited by recently radiated Ethiopian endemics, provide a wide spectrum of model situations for evolutionary studies. The extant species of endemic rodents, often markedly phenotypically differentiated, are expected to possess complex genetic features which evolved asa consequence of the interplay between geomorphology and past climatic changes. In this study, we used the largest available multi-locus genetic dataset of the murid genus Stenocephalemys (347 specimens from ca 40 localities across the known distributional area of all taxa) to investigate the relative importance of disruptive selection, temporary geographic isolation and introgression in their adaptive radiations in the Pleistocene. We confirmed the four main highly supported mitochondrial (mtDNA) clades that were proposed as four species in a previous pilot study: S. albipes is a sister species of S. griseicauda (both lineages are present on both sides of the GRV), while the second clade is formed by two Afro-alpine species, S. albocaudata (east of GRV) and the undescribed Stenocephalemys sp. A (west of GRV). There is a clear elevational gradient in the distribution of the Stenocephalemys taxa with two to three species present at different elevations of the same mountain range. Surprisingly, the nuclear species tree corresponded only a little to the mtDNA tree. Multispecies coalescent models based on six nuclear markers revealed the presence of six separate gene pools (i.e. candidate species), with different topology. Phylogenetic analysis, together with the geographic distribution of the genetic groups, suggests a complex reticulate evolution. We propose a scenario that involves (besides classical allopatric speciation) two cases of disruptive selection along the elevational ecological gradient, multiple crosses of GRV in dry and cold periods of the Pleistocene, followed by hybridization and mtDNA introgression on imperfect reproductive barriers. Spatial expansion of the currently most widespread "albipes" mtDNA clade was followed by population fragmentation, lineage sorting and again by hybridization and mtDNA introgression. Comparison of this genetic structure to other Ethiopian endemic taxa highlight the geographical areas of special conservation concern, where more detailed biodiversity studies should be carried out to prevent many endemic taxa from going extinct even before they are recognized.
Keywords: Animals; Ecosystem; Mitochondrial introgression; karyotyp; Haplotypes; cytochromy b; Rodentia; haplotypy; mitochondriální DNA; fylogeneze; Great Rift Valley; Murinae; Etiopie; molekulární evoluce; DNA, Mitochondrial; hybridizace genetická; Phylogeny; ekosystém; Ethiopian highlands; Ethiopia; zvířata; Ecological speciation; Cytochromes b; Hybridization, Genetic; Evolution, Molecular; Karyotype; Stenocephalemys